Tuning the mechanical properties of functionally graded nickel and aluminium alloy at the nanoscale. Issue 49 (15th September 2021) - Mitra, Shailee; Rahman, Md. Habibur; Motalab, Mohammad; Rakib, Tawfiqur; Bose, Pritom
Abstract : We revealed that the mechanical properties of Ni3 Al (homogeneous alloy) could be modulated utilizing functional grading. Abstract : In this article, Molecular Dynamics (MD) simulation is used to investigate the tensile mechanical properties of functional graded Ni–Al (Ni3 Al) alloy with Ni coating. The grading profile, temperature, crystallographic direction, and concentration of vacancy defects have been varied and corresponding changes in the tensile properties are reported. In general, it has been revealed that functional grading may reduce the ultimate tensile strength (UTS) of this homogeneous alloy but increase Young's modulus (YM). Furthermore, MD simulations suggest that elliptically graded Ni–Al alloy has the highest UTS at low temperature while at high temperature, the largest UTS is recorded for the parabolic grading. Besides, at any temperature, the parabolically graded Ni–Al alloy shows the largest YM, followed by linear grading and elliptical grading. Moreover, it is also observed that the [111] crystallographic direction for this alloy demonstrates the highest UTS and YM. At extremely low temperatures, lattice mismatch is also observed to exert a significant impact on the failure characteristics of functional graded Ni–Al alloys. This investigation also suggests that the vacancy defects introduced via removing either Al or Ni atoms degrades the UTS and YM of FGM alloys remarkably. Besides, it is also found that the UTS and YM of Ni–Al FGM alloys are very sensitive to Ni vacancies compared to Al vacancies. Parabolic grading demonstrates more resilience against vacancy defects, followed by linear and elliptical grading. This paper provides a comprehensive understanding of the mechanical properties of Ni–Al FGM alloys at the atomic level as a potential substitute for homogeneous alloys.